The Analysis of the Economic Inequality of the Coast Regions - Yulhendri Yulhendri; Inaya Sari Melati; Jean Elikal Marna; Weni Softazia (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
West and East coast of Sumatra are two different geographical and trade routes. The West Coast is connected with trade direction to India, Arabia and Africa while on the East Coast it is connected with trade in the Malacca Strait, East Asian economy. Based on photos of satellite images at night, the east coast has more light compared to the west coast. This study analyzed the differences in economic inequality between the economy of the population residing in the West Coast Region and the East Coast of Sumatra. This study took data sourced from the Indonesian Central Statistics Agency published in the last 5 years, 2013-2017. The data were processed using SPSS and Excel using the Williamson Index analysis tool. There are 23 Regencies / Cities in the West Coast and 23 Regencies / Cities in the East Coast analyzed where the West Coast average growth rate in the last 5 years is 5.17% and East Coast 5.48% with the Inequality index using the Williamson Index formula in West Coast 0.37 and East Coast 0.28. It was found that economic activity on the East Coast tends to be more lively and higher economic growth with a low level of inequality compared to the West coast of Sumatra